Quantifying the mode II critical strain energy release rate of borate bioactive glass coatings on Ti6Al4V substrates. (November 2017) - Matinmanesh, A.; Li, Y.; Clarkin, O.; Zalzal, P.; Schemitsch, E.H.; Towler, M.R.; Papini, M.
Abstract: Bioactive glasses have been used as coatings for biomedical implants because they can be formulated to promote osseointegration, antibacterial behavior, bone formation, and tissue healing through the incorporation and subsequent release of certain ions. However, shear loading on coated implants has been reported to cause the delamination and loosening of such coatings. This work uses a recently developed fracture mechanics testing methodology to quantify the critical strain energy release rate under nearly pure mode II conditions, G IIC, of a series of borate-based glass coating/Ti6Al4V alloy substrate systems. Incorporating increasing amounts of SrCO3 in the glass composition was found to increase the G IIC almost twofold, from 25.3 to 46.9 J/m 2 . The magnitude and distribution of residual stresses in the coating were quantified, and it was found that the residual stresses in all cases distributed uniformly over the cross section of the coating. The crack was driven towards, but not into, the glass/Ti6Al4V substrate interface due to the shear loading. This implied that the interface had a higher fracture toughness than the coating itself. Graphical abstract: fx1 Highlights: A method for studying the fracture properties of glass/Ti6Al4V systems was presented. The mode II critical strain energy release rate, G IIC, of the system was quantified. Increasing Sr 2+ content in the borate glass coating increased the G IIC of the system. The G IIC of these systems were 3-4 times higher than their G IC counterparts. The magnitude and distribution of residual stresses in the system were quantified.